"Strategic Lying": The Case of Brexit and the 2019 U.K. Election. (April 2022) - Gaber, Ivor; Fisher, Caroline
The final days of the Trump presidency and its aftermath brought into sharp focus the issue of political lying. Politicians have historically employed rhetoric and rhetorical spin to embellish the truth and hide damaging information. However, outright lying has traditionally been deemed politically too risky, resulting in resignation and the undermining of public trust. In contrast, recent electoral successes —the 2016 Brexit Referendum and the 2019 general election in the United Kingdom, and Trump's victory in 2016 and his increased electoral support in 2020—point to an apparent growing tendency for politicians caught lying not to be punished at the ballot box. Using the U.K. Brexit referendum and the 2019 general election as its case study, this conceptual paper argues that strategic political lying has been designed as a priming device to set the news agenda. As an effective campaigning tactic "strategic lying" represents a development of political spin—first evident in the mass media era—that has been intensified by the increasing professionalization of political communications and the rise of social media. In doing so, the concept of "strategic lying" theorized here contributes to deepening our understanding of the ongoing evolution of "spin" in the digital era.